Arctic stratospheric polar vortex collapse amplified South China extreme rainfall in April 2024 - Qilu Wang; Anmin Duan; Aiguo Dai; Shutao Cao; Aoqi Zhou; Yuan Gao; Chunyan Xiao; Bingxian Liu (npj Climate and Atmospheric Science)
Abstract In March 2024, the Arctic stratospheric polar vortex (ASPV) collapsed dramatically. The following April, extreme precipitation in South China (SCP) caused severe floods and economic damage. Whether and how they are connected is crucial yet unclear. Through observations and model simulations, we demonstrate that the ASPV collapse in March amplified extreme SCP in April 2024. As stratospheric anomalies persistently propagated downward, March ASPV had a pronounced impact on the North Atlantic tropospheric circulation in April, exciting eastward-propagating Rossby waves. The resulting lower-tropospheric cyclonic anomaly over South China enhanced vertical motion and moisture transport, with vertical ascent dominating the extreme precipitation. The ASPV’s influence on SCP ranked just behind that of El Niño-Southern Oscillation (ENSO), and together they improved SCP predictability to 52%. A weakened March ASPV increased extreme April SCP occurrence by 45%. This finding reveals a robust polar−low-latitude teleconnection, highlighting the Arctic stratospheric signal as a crucial predictor in SCP and even low-latitude climate, further aiding in impact mitigation.